An Enhanced Version of Combination of Multifocus Image Using Alpha Factor - Namrata; Maurya, Anamika (International Journal of Computer Sciences and Engineering, 2025)
Right and high quality image makes a huge difference, whether it can be any field of digital image processing. It is often not possible to get an image that contains every object in focus. To obtain an image that contains every object in focus a Multifocus image fusion process is required. In the process of image fusion good information from each of the given image is fused together to form a resultant image whose quality is far better than the any of the Multifocus input image. In this paper we proposed an algorithm which is the enhanced version of the existing algorithm. We utilize the concept of alpha factor and we vary the values of alpha factor according to our requirement. The proposed method is also compared with different methods. It is observed that proposed method preserves more information compared to earlier methods. It evaluates the performance of each algorithm with Matlab 2012a .We evaluate the algorithm by using performance parameter peak signal to noise ratio and the mean square error value